Experimental Investigations on the Effect of Reinforcement Coating on Magnesium Composites for Automotive Brake Pad. (18th February 2022) - Venugopal, S.; Karikalan, L.; Kumar, R.
Abstract : The braking system is an important component in the automobile sector for transportation. To stop or slow down the vehicle safely, the friction brakes are employed by converting the kinetic energy to heat energy by friction. The interaction of surface materials such as rotor and pad produces heat due to friction and those materials should have a thermally stable tendency to deal with the heat than wear resistance. In this study, for the first time, an attempt is made to check the possibilities of introducing the Mg composite into brake pad applications. The inorganic type friction materials with various components of materials are constantly growing to get the high-performance and low-cost brake pad for commercial vehicles. The Mg composite is reinforced with electroless Ni-P-coated alumina and silicon carbide microparticles using the parameter optimized stir-squeeze method. The particles are coated by using the electroless method and various Mg composites such as Mg alloy, Mg + coated Al2 O3, Mg + coated Al2 O3, Mg + coated Al2 O3, and SiC are prepared. The tribological properties of the newly formulated magnesium composite are premeditated using a tribometer. The brake pad (Mg composite) material is used as a pin, and the disc material (stainless steel) is used as a plate for the experiments. Characterization of the composites is done using a FESEM machine with the attachment of EDAX to measure the elements present in the composite. The results revealed that porosity reduced significantly for the composite which has coated reinforcements. The hardness and compression strength of the composite are also enhanced for the composite which has coated reinforcements. The wear resistance of the prepared Mg composite is closer to other brake pad data, and thus, the material can be used as friction material for automotive brake pad applications.